PENERAPAN METODE EKSPERIMEN DALAM PENINGKATAN PEMBELAJARAN IPA TENTANG SIFAT CAHAYA KELAS V SDN KLOPOGODO - Estu, Eka (KALAM CENDEKIA PGSD KEBUMEN, 2013)
Application of Improved Method of Learning Science Experiments in Class V. This study aimed to describe the steps in the application of the experimental method of learning about the nature of science Light on the SDN Klopogodo fifth grade students, to describe the behavior of students in the following subjects, and to identify improved learning outcomes in science learning about the properties of light in the fifth grade students of SDN Klopogodo by applying the experimental method. This study uses classroom action research conducted in three cycles, each cycle includes the planning, implementation, observation and reflection. The results showed that the application of the experimental method in science teaching fifth grade can improve measures of learning, the behavior of students in the following subjects, as well as student learning outcomes. Keywords: experimental methods, learning, learning outcomes